Análise das alterações musculares de ratos obesos frente a intervenção do exercício de natação – um estudo envolvendo a composição corporal, morfologia muscular e citocinas circulantes. - Arrais-Lima, Cristina (2020)
Obesity has a multifactorial character and may be related to hereditary, pharmacological factors and especially to unbalanced diets. The accumulation of fat can occur in different tissues and places in the body, bringing different consequences. The fats that accumulate in the abdomen, the so-called visceral or central fats, seem to not only correlate with metabolic diseases, such as type II diabetes mellitus, high blood pressure and cardiovascular diseases, but also with some types of cancer and cause mild chronic systemic inflammation . This condition has become a public health problem and millions are spent each year fighting overweight and obesity, not only in adults, but also in children and adolescents worldwide. In the literature, the treatment for obesity is multidisciplinary, but in general it is necessary to balance the intake with the energy expenditure, and for this, exercises are the most recommended tools in non-medicated treatments. Therefore, this thesis work consists of 2 studies: Study 1, the objective was to verify the changes caused by obesity in the parameters of body weight, in the percentage of body and abdominal fat and bone mass in obese rats through the body scan done by the device Dual-Energy X-ray absorptiometry Scan (HOLOGIC ®) pre and post swimming training. Also, correlate these measures with hormones linked to the imbalance caused by obesity, such as Leptin, and the attempt to return to metabolic balance, such as adiponectin and irisin. These measurements were made after swimming training, which was chosen because of the non-overload caused in the joints. Study 2 aimed to verify the accumulation of fat in the musculoskeletal tissue, especially in the vastus medialis, vastus lateralis, anterior tibialis and gastrocnemius muscles and to analyze the circulating cytokines, in order to investigate the systemic inflammation caused by obesity. In this study we analyzed the cytokines IL-4 and IL-10, considered anti-inflammatory and TNFα and IL-6, pro-inflammatory. The results showed that swimming in obese rats promoted a reduction in central and body fat, as well as an increase in the concentration of IL-4 in only obese animals, showing an attempt to recover the metabolic balance. From these studies, we identified that swimming was effective in modulating the accumulated fat in the abdomen, as well as in the studied muscles, of obese rats. These results collaborate with the literature on exercise as a tool, not medicated, to combat obesity and its changes, even without any intervention in the diet.